3D bone-shape changes and their correlations with cartilage T1ρ and T2 relaxation times and patient-reported outcomes over 3-years after ACL reconstruction. Issue 6 (June 2019) - Zhong, Q.; Pedoia, V.; Tanaka, M.; Neumann, J.; Link, T.M.; Ma, B.; Lin, J.; Li, X.
Summary: Purpose: (1) To identify bone-shape changes from baseline to 3-years after anterior cruciate ligament reconstruction (ACLR). (2) to assess association between changes in bone-shape from baseline to 6-months and changes in cartilage matrix and patient functions and symptoms from baseline to 3-years after ACLR. Methods: Bilateral knees of 30 patients with unilateral ACL injuries were scanned at baseline, 6-months, 1-, 2-, and 3-years after ACLR. Bilateral knees of 13 controls were scanned at baseline, 1- and 3-years. Mean T1ρ and T2 values of each cartilage compartment were computed. Bone shape was quantified using statistical shape modeling (SSM) and 3D-MRI. Patient functions and symptoms were evaluated using Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: Statistically significant changes were observed in Femur 2 (medial femoral condyle [MF] shape), Femur 6 (intercondylar notch width), Tibia 1 (tibia plateau area), and Tibia 7 (medial tibia slope) over 3-years after ACLR. Statistically significant differences were observed between injured and control knees in several modes. Statistically significant correlations were found between changes in bone shape (ΔFemur 6, ΔFemur 8 [trochlea inclination and MF height], ΔTibia 1) from baseline to 6-months and that of cartilage T1ρ and T2 and KOOS from baseline to 3-years after ACLR. Conclusion: Bone shape remodeling occurs after ACLR, and early bone shape changes (within 6 months) correlated with cartilage matrix and patient outcomes at 3-years after ACLR. Bone shape can be a promising imaging biomarker that stratifies patients at high risk for post-traumatic osteoarthritis (PTOA).